Effect of barley preservation method on milk production and milk quality in organic farming - Adler, Steffen A.; Randby, Åshild T. (Nordic Association of Agricultural Scientists (NJF), Section I: Soil, Water and Environment, Swedish University of Agricultural Sciences, 2005)
The effect of dried vs. ensiled barley (cv. Arve) on feed intake, milk yield and quality in organic production was tested in two experiments in Northern Norway. In the first experiment, two groups were given either 40% or 10% concentrated feed (barley) per cow and year, calculated on energy basis. Grass silage was fed ad. lib. Both drying and ensiling preserved barley properly and resulted in approximately the same feed intake and milk production. Cows in the group with 10% barley had lower milk protein concentration than cows in the group with 40% barley. The palatability of barley was in general low, and several cows refused parts of their allowances throughout the experiment. The second experiment had a cross over design with three treatments. The trial was designed to evaluate the effect of preservation method for barley on sensoric milk quality. The cows were fed well-preserved grass silage ad lib. and supplemented with 5.8 kg DM of either dried barley, barley ensiled with molasses, or barley ensiled with a propionic acid-containing additive. All types of barley were well preserved and no negative effect of ensiled barley was observed.